A prospective study on association of serum uric acid level with knee osteoarthritis - Jain, Siddharth; Jain, Mudit (International Journal of Medical Research and Review, 2016)
Background: A numbers of studies have described a relationship among serum uric acid level and generalized osteoarthritis in recent past, but studies on evidence of relationship among serum uric acid and knee joint osteoarthritis are limited. Present study is intended to validate the association between serum uric acid levels and osteoarthritis of kne joint. Methods: This is a prospective study including three hundred forty patients (225 males, 115 females) with clinically diagnosed osteoarthritis of knee. Patient’s radiographs of affected knees and hands were obtained along with their serum uric acid level, Rheumatoid factor and C reactive protein level. Keligren-Lawrence osteoarthritis scale was used for grading of knee osteoarthritis roentgenographically. On the basis of serum uric acid levels, all the patients were divided in to three groups acoording to serum uric acid level Group 1: - serum uric acid less than 5mg/dl, Group 2: - serum uric acid levels between 5.1-7 mg/dl, Group 3: - serum uric acid levels greater than 7 mg/dl. Results: Out of 340 patients, 238 patients (70 %) dignosed as isolated knee joint osteoarthritis, generalized osteoarthritis is seen in 66 (19.6 %) patients, and Rheumatoid Factor, along with C-reactive protein is positive in 36(10.5%) patients. Association of osteoarthritis of knee joint, generalized osteoarthritis with the highest tertile of serum uric acid level found to be strongly positive [adjusted odds ratio- 2.31 and adjusted odds ratio- 3.27 respectively). Also association between increasing serum uric acid levels and progression of the osteoarthritis of knee found to be positive. Conclusion: This study supports a possible correlation between hyperuricemia and osteoarthritis. also a positive association of knee joint osteoarthritis, generalized osteoarthritis progression with increasing uric acid level is suggested.